2023
DOI: 10.1002/agg2.20435
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of substrate inoculation with Pseudomonas strains on tomato phenology, yield, and selected human health‐related phytochemical compounds

Muazu Issifu,
Labode Hospice Stevenson Naitchede,
Elijah Miinda Ateka
et al.

Abstract: Plant growth‐promoting rhizobacteria enhances nutritional availability during root colonization. Pseudomonas is the most popular bioinoculant due to its synergistic effects on plant development. This study evaluated the impact of four Pseudomonas strain substrate inoculations on tomato phenology, yield, and selected phytochemical components relevant to human health. The bacterial isolates have been characterized morphologically, biochemically, physiologically, and phylogenetically. Tomato plants on cocopeat su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
0
0
0
Order By: Relevance
“…Issifu, et al 2023 [39] demonstrate that Pseudomonas strains enhance plant growth, yield, and the presence of healthrelated phytochemical substances in tomato fruits. In another research, Alzate Zuluaga, et al 2021 [40] reported that the application of bacterial consortia led to a signifi cant increase in the number of trusses per plant.…”
Section: Resultsmentioning
confidence: 99%
“…Issifu, et al 2023 [39] demonstrate that Pseudomonas strains enhance plant growth, yield, and the presence of healthrelated phytochemical substances in tomato fruits. In another research, Alzate Zuluaga, et al 2021 [40] reported that the application of bacterial consortia led to a signifi cant increase in the number of trusses per plant.…”
Section: Resultsmentioning
confidence: 99%